2021
DOI: 10.1249/mss.0000000000002768
|View full text |Cite
|
Sign up to set email alerts
|

Personal Activity Intelligence e-Health Program in People with Type 2 Diabetes: A Pilot Randomized Controlled Trial

Abstract: Introduction: Innovative strategies are needed to enable people with type 2 diabetes (T2D) to self-manage physical activity (PA). Personal Activity Intelligence (PAI) is a new metric that uses the heart rate response to PA to inform the user as to whether they are doing enough PA to reduce the risk of premature mortality. The PAI score reflects PA over the previous 7 d with the goal to maintain a score ≥100. The aim of this study was to investigate the feasibility, acceptability, and efficacy of the PAI e-Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 35 publications
4
33
0
Order By: Relevance
“…At the end of the trial period, many participants indicated they were intending to continue to wear the smartwatch and monitor PAI or were still considering continuation. This is line with the pilot randomised PAI e-health program used for people with type 2 diabetes which reported 80% of participants intended to continue PAI monitoring [ 9 ]. Participants stated they would recommend the device to others based on their interest in the PAI concept and its ability to monitor their health.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…At the end of the trial period, many participants indicated they were intending to continue to wear the smartwatch and monitor PAI or were still considering continuation. This is line with the pilot randomised PAI e-health program used for people with type 2 diabetes which reported 80% of participants intended to continue PAI monitoring [ 9 ]. Participants stated they would recommend the device to others based on their interest in the PAI concept and its ability to monitor their health.…”
Section: Discussionsupporting
confidence: 79%
“…Several studies utilising the PAI algorithm have been conducted across China and America [ 25 , 35 37 , 51 ]. Recently, a randomised controlled trial was implemented which monitored PAI in people with diabetes [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“… 29 Others demonstrated that individuals with type 2 diabetes using PAI (PAI-App and wearable heart rate monitor) over 12 weeks significantly increased their exercise capacity and sleep time, and decreased body fat percentage and sex-specific adiposity when compared with their peers following contemporary PA recommendations. 16 The introduction of PAI in everyday life has the potential to turn a theoretical association of PA into a daily encouraging process through monitoring and challenging the device-wearer to achieve a practical goal every day. Sharing this metric with physicians may motivate and encourage patients to augment their PA to increase weekly PAI scores.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy individuals who regularly attain a weekly PAI score ≥100 have high age- and sex-specific CRF levels, more favourable cardiovascular risk factor profiles 14 , 16 , 17 and a lower risk of all-cause and cardiovascular mortality when compared with their inactive counterparts, independent of whether contemporary PA recommendations are met or not. 18 , 19 Regularly obtaining a weekly PAI score ≥100 has also been associated with a reduced risk of premature mortality in patients with established cardiovascular disease (CVD) 20 when compared with their inactive counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation